Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có :
\(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)+1\)
\(=\left[\left(x+1\right)\left(x+4\right)\right]\left[\left(x+2\right)\left(x+3\right)\right]+1\)
\(=\left(x^2+5x+4\right)\left(x^2+5x+6\right)+1\)
Đặt \(x^2+5x+5=t\)
=> Đa thức trở thành
\(\left(t-1\right)\left(t+1\right)+1\)
\(=t^2-1+1\)
\(=t^2\)
Thay vào ta được
Đt=\(\left(x^2+5x+5\right)^2\)
\(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)+1\)
\(=\left[\left(x+1\right)\left(x+4\right)\right]\left[\left(x+2\right)\left(x+3\right)\right]+1\)
\(=\left(x^2+5x+4\right)\left(x^2+5x+6\right)+1\) (1)
Đặt \(x^2+5x+5=t\) thì (1)
\(\Leftrightarrow\left(t-1\right)\left(t+1\right)+1=t^2-1+1=t^2=\left(x^2+5x+5\right)^2\)
\(x^3-3x^2+3x-1-y^3\)
\(=\left(x-1\right)^3-y^3\)
\(=\left(x-1-y\right)\left[\left(x-1\right)^2+y\left(x-1\right)+y^2\right]\)
\(=\left(x-y-1\right)\left[\left(x-1\right)\left(x-1+y\right)+y^2\right]\)
\(x^3-3x^2+3x-1-y^3\\ =\left(x-1\right)^3-y^3\\ =\left(x-1-y\right)\text{[ (x-1)^2+y(x-1)+y^2}\)
\(=\left(x-y-1\right)\left[\left(x-1\right)\left(x-1+y\right)+y^2\right]\)
a,\(8x^2-8xy+2x=2x\left(4x-8y+1\right)\)
b,\(\left(x^2+2x\right)\left(x^2+4x+3\right)-24=x\left(x+2\right)\left(x+1\right)\left(x+3\right)-24\)
\(=\left(x^2+3x\right)\left(x^2+3x+2\right)-24=\left(t+1\right)\left(t-1\right)-24=t^2-5^2=\left(t+5\right)\left(t-5\right)\)
\(=\left(x^2+3x+6\right)\left(x^2+3x-4\right)\)( đặt t = x2 + 3x + 1 )
\(x^3-4x^2-12x+27\)
\(=x^3+3x^2-7x^2-21x+9x+27\)
\(=x^2\left(x+3\right)-7x\left(x+3\right)+9\left(x+3\right)\)
\(=\left(x^2-7x+9\right)\left(x+3\right)\)
Ta có :
\(x^4+4\)
\(=\left(x^2\right)^2+2.x^2.2+2^2-\left(2x\right)^2\)
\(=\left(x^2+2\right)^2-\left(2x\right)^2\)
\(=\left(x^2+2-2x\right)\left(x^2+2+2x\right)\)
\(x^3+9x^2+26x+24=\left(x^2+7x+12\right)\left(x+2\right)=\left(x+3\right)\left(x+4\right)\left(x+2\right)\)
Ta có: \(x^3+9x^2+26x+24\)
\(=\left(x^3+2x^2\right)+\left(7x^2+14x\right)+\left(12x+24\right)\)
\(=x^2\left(x+2\right)+7x\left(x+2\right)+12\left(x+2\right)\)
\(=\left(x+2\right)\left(x^2+7x+12\right)\)
\(=\left(x+2\right)\left[\left(x^2+3x\right)+\left(4x+12\right)\right]\)
\(=\left(x+2\right)\left[x\left(x+3\right)+4\left(x+3\right)\right]\)
\(=\left(x+2\right)\left(x+3\right)\left(x+4\right)\)
Ta có:
x4+2x3+x2+x+1=(x2)2+2.x2.x+x2+x+1
=(x2+x)+(x+1)
=x2+2x+1
=(x+1)2
\(2x^3-5x^2+2x=x.\left(2x^2-5x+2\right)\)
\(=x.\left[\left(2x^2-4x\right)-\left(x-2\right)\right]\)
\(=x.\left[2x\left(x-2\right)-\left(x-2\right)\right]\)
\(=x.\left(x-2\right)\left(2x-1\right)\)
\(x^4+2x^2-24\)
Đặt \(t=x^2\) ta có:
\(t^2+2t-24=t^2-4t+6t-24\)
\(=t\left(t-4\right)+6\left(t-4\right)\)
\(=\left(t+6\right)\left(t-4\right)\)
\(=\left(x^2+6\right)\left(x^2-4\right)\)
\(=\left(x-2\right)\left(x+2\right)\left(x^2+6\right)\)